Clinical phenotypes of acute heart failure based on signs and symptoms of perfusion and congestion at emergency department presentation and their relationship with patient management and outcomes. (18th June 2019) - Javaloyes, Patricia; Miró, Òscar; Gil, Víctor; Martín‐Sánchez, Francisco Javier; Jacob, Javier; Herrero, Pablo; Takagi, Koji; Alquézar‐Arbé, Aitor; López Díez, María Pilar; Martín, Enrique; Bibiano, Carlos; Escoda, Rosa; et al.
Abstract : Objective: To compare the clinical characteristics and outcomes of patients with acute heart failure (AHF) according to clinical profiles based on congestion and perfusion determined in the emergency department (ED). Methods and results: Overall, 11 261 unselected AHF patients from 41 Spanish EDs were classified according to perfusion (normoperfusion = warm; hypoperfusion = cold) and congestion (not = dry; yes = wet). Baseline and decompensation characteristics were recorded as were the main wards to which patients were admitted. The primary outcome was 1‐year all‐cause mortality; secondary outcomes were need for hospitalisation during the index AHF event, in‐hospital all‐cause mortality, prolonged hospitalisation, 7‐day post‐discharge ED revisit for AHF and 30‐day post‐discharge rehospitalisation for AHF. A total of 8558 patients (76.0%) were warm + wet, 1929 (17.1%) cold + wet, 675 (6.0%) warm + dry, and 99 (0.9%) cold + dry; hypoperfused (cold) patients were more frequently admitted to intensive care units and geriatrics departments, and warm + wet patients were discharged home without admission. The four phenotypes differed in most of the baseline and decompensation characteristics. The 1‐year mortality was 30.8%, and compared to warm + dry, the adjusted hazard ratios were significantly increased for cold + wet (1.660; 95% confidence interval 1.400–1.968) and cold + dry (1.672; 95% confidence interval 1.189–2.351). Hypoperfused (cold) phenotypes also showed higher rates of index episode hospitalisation and in‐hospital mortality, while congestive (wet) phenotypes had a higher risk of prolonged hospitalisation but decreased risk of rehospitalisation. No differences were observed among phenotypes in ED revisit risk. Conclusions: Bedside clinical evaluation of congestion and perfusion of AHF patients upon ED arrival and classification according to phenotypic profiles proposed by the latest European Society of Cardiology guidelines provide useful complementary information and help to rapidly predict patient outcomes shortly after ED patient arrival.